Adverse Prognostic Impact of Postoperative Complications After Gastrectomy for Patients With Stage II/III Gastric Cancer: Analysis of Prospectively Collected Real-World Data - Song, Jeong Ho; Lee, Sejin; Choi, Seohee; Cho, Minah; Kwon, In Gyu; Kim, Yoo Min; Son, Taeil; Kim, Hyoung-Il; Jung, Minkyu; Hyung, Woo Jin (Frontiers in Oncology, 2021)
Background: The impact of postoperative complications on the prognosis of gastric cancer remains controversial. This study aimed to evaluate the relationship between postoperative complications and long-term survival in patients undergoing gastrectomy for stage II/III gastric cancer. Methods: Some 939 patients underwent curative gastrectomy for stage II/III gastric cancer were identified from real-world data prospectively collected between 2013 and 2015. We divided patients according to the presence of serious complications, specifically, Clavien-Dindo grade III or higher complications or those causing a hospital stay of 15 days or longer. Results: Serious complications occurred in 125 (13.3%) patients. Patients without serious complications (64.3%) completed adjuvant chemotherapy significantly more than patients with serious complications (37.6%; p<0.001). The 5-year overall survival(OS) rate was 58.1% and recurrence-free survival(RFS) rate was 58.1% in patients with serious complications, which were significantly worse than those of patients without serious complications (73.4% and 74.7%, respectively; p<0.001 for both). In stage II, once patients completed adjuvant chemotherapy adequately, the OS and RFS of patients with serious complications did not differ from those without serious complications. However, in stage III, the patients with serious complications showed a worse OS even after completion of adequate adjuvant chemotherapy. Conclusion: Serious complications after gastrectomy had a negative impact on the prognosis of stage II/III gastric cancer patients. Serious complications worsen the survival in association with inadequate adjuvant chemotherapy. Efforts to reduce serious complications, as well as support adequate chemotherapy through proper management of serious complications, would improve the prognosis of stage II/III gastric cancer patients.